USE OF INNOVATIVE METHODS IN TEACHING MATHEMATICS IN PROFESSIONAL EDUCATION SCHOOLS - Kochkaya Sattarova Dilrabo (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article focuses on the current issues of teaching mathematics in professional educational institutions. Attention is also paid to the content of reforms and legal documents implemented in the field.